Monitoring of real interaction in marketing websites: Australia and Portugal's perspective - Issa, Tomayess; Isaias, P. (ACM Inc, 2012)
This paper discusses the importance of monitoring real interaction in marketing websites. Real interaction becomes indispensable in marketing websites, as designers can track users’ behaviour toward the website to achieve both users and designers specific objectives. Real interaction has been either not fully considered or totally ignored in methodologies for information systems, marketing, and website development, as it needs training and specialists to interpret the statistical outcomes. This empirical evidence was collected using quantitative and qualitative approaches, which were employed in both Australia and Portugal. Survey data were gathered from 103 Australian and Portuguese respondents. The study released interesting results, which indicated that real interaction is very important in the website development process, in attracting more users to the websites and increasing the client’s profit. It is important that clients should respond rapidly to users’ comments. Finally, before real interaction is adopted in the website development process, privacy and security should be considered.